Triptolide reverses hypoxia‐induced epithelial–mesenchymal transition and stem‐like features in pancreatic cancer by NF‐κB downregulation. Issue 10 (19th November 2013) - Liu, Li; Salnikov, Alexei V.; Bauer, Nathalie; Aleksandrowicz, Ewa; Labsch, Sabrina; Nwaeburu, Clifford; Mattern, Jürgen; Gladkich, Jury; Schemmer, Peter; Werner, Jens; Herr, Ingrid
<x xml:space="preserve">Abstract</x> Pancreatic ductal adenocarcinoma (PDA) is one of the most lethal malignancies characterized by an intense tumor stroma with hypoperfused regions, a significant inflammatory response and pronounced therapy resistance. New therapeutic agents are urgently needed. The plant‐derived agent triptolide also known as "thunder god vine" has a long history in traditional Chinese medicine for treatment of rheumatoid arthritis and cancer and is now in a clinical phase II trial for establishing the efficacy against a placebo. The authors mimicked the situation in patient tumors by induction of hypoxia in experimental models of pancreatic cancer stem cells (CSCs) and evaluated the therapeutic effect of triptolide. Hypoxia led to induction of colony and spheroid formation, aldehyde dehydrogenase 1 (ALDH1) and NF‐κB activity, migratory potential and a switch in morphology to a fibroblastoid phenotype, as well as stem cell‐ and epithelial–mesenchymal transition‐associated protein expression. Triptolide efficiently inhibited hypoxia‐induced transcriptional signaling and downregulated epithelial–mesenchymal transition (EMT) and CSC features in established highly malignant cell lines, whereas sensitive cancer cells or nonmalignant cells were less affected. In vivo triptolide inhibited tumor take and tumor growth. In primary CSCs isolated from patient tumors, triptolide downregulated markers of CSCs, proliferation and mesenchymal cells along with upregulation of markers for apoptosis and epithelial cells. This study is the first to show that triptolide reverses EMT and CSC characteristics and therefore may be superior to current chemotherapeutics for treatment of PDA.